REM-associated sleep apnoea: prevalence and clinical significance in the HypnoLaus cohort. Issue 2 (16th August 2018) - Acosta-Castro, Patricia; Hirotsu, Camila; Marti-Soler, Helena; Marques-Vidal, Pedro; Tobback, Nadia; Andries, Daniela; Waeber, Gérard; Preisig, Martin; Vollenweider, Peter; Haba-Rubio, José; Heinzer, Raphael
This study determined the prevalence of rapid eye movement (REM) related sleep-disordered breathing (REM-SDB) in the general population and investigated the associations of REM-SDB with hypertension, metabolic syndrome, diabetes and depression. Home polysomnography (PSG) recordings (n=2074) from the population-based HypnoLaus Sleep Cohort (48.3% men, 57±11 years old) were analysed. The apnoea–hypopnoea index was measured during REM and non-REM sleep (as REM-AHI and NREM-AHI, respectively). Regression models were used to explore the associations between REM-SDB and hypertension, diabetes, metabolic syndrome and depression in the entire cohort and in subgroups with NREM-AHI <10 events·h −1 and total AHI <10 events·h −1 . The prevalence of REM-AHI ≥20 events·h −1 was 40.8% in the entire cohort. An association between increasing REM-AHI and metabolic syndrome was found in the entire cohort and in both the NREM-AHI and AHI subgroups (p-trend=0.014, <0.0001 and 0.015, respectively). An association was also found between REM-AHI ≥20 events·h −1 and diabetes in both the NREM-AHI <10 events·h −1 (odds ratio (OR) 3.12 (95% CI 1.35–7.20)) and AHI <10 events·h −1 (OR 2.92 (95% CI 1.12–7.63)) subgroups. Systolic and diastolic blood pressure were positively associated with REM-AHI ≥20 events·h −1 . REM-SDB is highly prevalent in our middle-to-older age sample and is independently associated with metabolic syndrome and diabetes. These findings suggest that an increase in REM-AHI could be clinically relevant. REM sleep-disordered breathing is highly prevalent and is associated with metabolic syndrome and diabetes http://ow.ly/u52H30kBh3u